Incorporating Open/Free GIS and GPS Software in Power Transmission Line Routine Work: The Case of Crete and Rhodes - Pylarinos, D.; Pellas, I. (Engineering, Technology & Applied Science Research, 2017)
Geographical Information System (GIS) and Global Positioning System (GPS) software are widely gaining attention in power system planning and operation. Although commercial systems are increasingly being incorporated in power systems applications, they are yet to be fully incorporated in the routine work of utilities (and especially in the work of crews), due to several reasons such as cost, portability, connectivity, performance/speed, infrastructure etc. This paper focuses on incorporating certain open/free GIS and GPS software in routine transmission line work. The case study is the 150kV transmission systems of the Greek islands of Crete and Rhodes which show increased complexity due to certain localized factors such as Greek legislation, the diverse terrain/routes, the segmented design due to the network’s growth over the years (regarding both voltage levels and routes) and the use of different Coordinate Reference Systems (or Geodetic Systems) from the Greek state. The main goals of this work was to incorporate open/free software that provided limitless online access points, offline navigation and a user friendly design that wouldn’t require any additional training, programming etc. The basic scheme described in this paper can be followed to provide similar results in other applications.